Can we use digital life-log images to investigate active and sedentary travel behaviour? Results from a pilot study - Kelly, Paul; Doherty, Aiden; Berry, Emma; Hodges, Steve; Batterham, Alan M.; Foster, Charlie (International Journal of Behavioral Nutrition and Physical Activity, 2011)
Active travel such as walking and cycling has potential to increase physical activity levels in sedentary individuals. Motorised car travel is a sedentary behaviour that contributes to carbon emissions. There have been recent calls for technology that will improve our ability to measure these travel behaviours, and in particular evaluate modes and volumes of active versus sedentary travel. The purpose of this pilot study is to investigate the potential efficacy of a new electronic measurement device, a wearable digital camera called SenseCam, in travel research.